2021
DOI: 10.3390/rs13051032
|View full text |Cite
|
Sign up to set email alerts
|

The Decrease in Lake Numbers and Areas in Central Asia Investigated Using a Landsat-Derived Water Dataset

Abstract: : Although Central Asia has a strong continental climate with a constant moisture deficit and low relative humidity, it is covered by thousands of lakes that are critical to the sustainability of ecosystems and human welfare in the region. Vulnerability to climate change and anthropogenic activities have contributed to dramatic inter-annual and seasonal changes of the lakes. In this study, we explored the high spatio–temporal dynamics of the lakes of Central Asia using the terraPulse™ monthly Landsat-derived s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…Arid zones are more sensitive than other areas to temperature changes during global climate change, especially desert areas (Chen et al, 2015;Huang et al, 2016;Liang et al, 2020). Remote sensing data show that the lake areas in the BJD and central Asia have decreased in recent decades (Zhang et al, 2013;Che et al, 2021). With ongoing global warming, our results suggest that lakes in arid areas, especially in desert areas, will become increasingly salty, and this issue should have been addressed earlier.…”
Section: The Factors Influencing Lake Evolutionmentioning
confidence: 68%
See 1 more Smart Citation
“…Arid zones are more sensitive than other areas to temperature changes during global climate change, especially desert areas (Chen et al, 2015;Huang et al, 2016;Liang et al, 2020). Remote sensing data show that the lake areas in the BJD and central Asia have decreased in recent decades (Zhang et al, 2013;Che et al, 2021). With ongoing global warming, our results suggest that lakes in arid areas, especially in desert areas, will become increasingly salty, and this issue should have been addressed earlier.…”
Section: The Factors Influencing Lake Evolutionmentioning
confidence: 68%
“…Furthermore, dry basins or shrinking lakes in the geological period also occurred under the high temperature and precipitation climate in the northeastern Tibetan Plateau and Hexi Corridor (Liu et al, 2013;Wang et al, 2014;Wu et al, 2020). Therefore, for other areas of the world, although there are differences in the timing of temperature increases, they all lead to droughts and extreme events (Hegerl et al, 2018;Neukom et al, 2019;Woolway et al, 2020;Che et al, 2021).…”
Section: The Factors Influencing Lake Evolutionmentioning
confidence: 99%
“…The increasing of evaporation of land surface which decreases the lake surface area in the low elevation and plain regions, while the melting of glaciers leads to the formation of new lakes in the high elevation regions [4]. In the past few decades, a widespread water loss occured in the global endorheric system [5] and total lake area in Central Asia exhibited a decreased trend [6][7][8]. Previous study have shown that nine lakes in the Central Asia lost their area about 45,352 km 2 , which accounts for approximately 49.62% of their total surface area [6] and the number of lake decreased from 7309 in 2000 to 6585 in 2015, with a decline rate of 85 lakes per year [7].…”
Section: Introductionmentioning
confidence: 99%
“…In the past few decades, a widespread water loss occured in the global endorheric system [5] and total lake area in Central Asia exhibited a decreased trend [6][7][8]. Previous study have shown that nine lakes in the Central Asia lost their area about 45,352 km 2 , which accounts for approximately 49.62% of their total surface area [6] and the number of lake decreased from 7309 in 2000 to 6585 in 2015, with a decline rate of 85 lakes per year [7]. Hence, global climate change greatly affects the evolution of lakes.…”
Section: Introductionmentioning
confidence: 99%
“…As an important part of the global hydrological and biogeochemical water cycle, lakes play an important role in runoff regulation, water recharge, and the ecological balance of watersheds [ 1 , 2 , 3 ]. Their formation and disappearance, expansion and contraction, and evolution of the surrounding ecosystem are the results of complex interactions of global, regional, and local tectonic and climatic events [ 4 ].…”
Section: Introductionmentioning
confidence: 99%